An information discovery scheme for IoS of agricultural services using improved chord-ONS model. (2018) - Fu, Baojun
To solve the problems in EPC early network discovery service mode, we have analysed many aspects, such as load balance, robustness, and content privacy. We explain the architecture and workflow of structured P2P based ONS resolution system, and analyse advantages and disadvantages of current P2P-ONS system. Then the improved scheme is put forward which adopts hierarchical P2P network architecture to form ONS resolution system. It proposes a two-level chord-ONS architecture including routing performance analysis, storage and query of system information, nodes joining in or out, and selection of super nodes. The routing strategy based on node performance for super nodes and common nodes is also put forward. By the analysis of simulation results we find that the improved routing mechanism is better than the structured chord routing mechanism in query hopping, query delay and stability. It is more suitable for internet of things with huge dynamic and huge amount of information and it also shows comprehensive performance compared to traditional structured P2P network.